THE USE OF PROMPTING AND CONSEQUATING BEHAVIOURS IN STIMULATING CHILDREN TO USE ENGLISH AS THEIR SECOND LANGUAGE: A STUDY OF TWO INDONESIAN FAMILIES - Linggayani Soentoro; Heny Hartono; Emilia Ninik (Soegijapranata Catholic University, 2006)
: English in Indonesia is still as a foreign language. Yet, there has been a growing need within Indonesian society to raise the children in bilingual or multilingual context by having English as a second language within the families. This article is a report on the research of two nuclear Indonesian families who stimulate their children to use English as the second language. The researched has been done through three procedures, i.e. recording, observation, and interview. In stimulating their children in using English, the parents used several ways, like prompting and consequating behaviours. Yet, the mix of two languages in using those ways made the results of this research unique and special. This article reports about the ways used by the parents. It is found that parents apply prompting but they only apply imitation for consequanting behaviours. It is also found some unique phenomenon that occurred in stimulating the children to use English language.